Large‐scale migrations of brown bears in Eurasia and to North America during the Late Pleistocene. (15th November 2017) - Anijalg, Peeter; Ho, Simon Y. W.; Davison, John; Keis, Marju; Tammeleht, Egle; Bobowik, Katalina; Tumanov, Igor L.; Saveljev, Alexander P.; Lyapunova, Elena A.; Vorobiev, Alexandr A.; Markov, Nikolai I.; Kryukov, Alexey P.; et al.
Abstract: Aim: Climatic changes during the Late Pleistocene had major impacts on populations of plant and animal species. Brown bears and other large mammals are likely to have experienced analogous ecological pressures and phylogeographical processes. Here, we address several unresolved issues regarding the Late Pleistocene demography of brown bears: (1) the putative locations of refugia; (2) the direction of migrations across Eurasia and into North America; and (3) parallels with the demographic histories of other wild mammals and modern humans. Location: Eurasia and North America. Methods: We sequenced 110 complete mitochondrial genomes from Eurasian brown bears and combined these with published sequences from 138 brown bears and 33 polar bears. We used a Bayesian approach to obtain a joint estimate of the phylogeny and evolutionary divergence times. The inferred mutation rate was compared with estimates obtained using two additional methods. Results: Bayesian phylogenetic analysis identified seven clades of brown bears, with most individuals belonging to a very large Holarctic clade. Bears from the widespread clade 3a1, which has a distribution from Europe across Asia to Alaska, shared a common ancestor about 45, 000 years ago. Main conclusions: We suggest that the Altai‐Sayan region and Beringia were important Late Pleistocene refuge areas for brown bears and propose large‐scale migration scenarios for bears in Eurasia and to North America. We also argue that brown bears and modern humans experienced a demographic standstill in Beringia before colonizing North America.